EFEKTIFITAS INTERVENSI DEEP BREATHING EXERCISE TERHADAP SATURASI OKSIGEN PENDERITA ASMA - khalid mustofa; Rina Loriana; Mustaming Mustaming (MNJ (Mahakam Nursing Journal), 2022)
Abstract Pravels of asthma sufferers worldwide increased from 235 million in 2011 to 334 million in 2014. (Global Asthma Network, 2014). This study aims to identify the most effective interventions of slow deep breathing exercise and deep breathing exercise for oxygen saturation changes in asthmatics. This research is Quasi Experiment with pre and post test group design randomise design. The population in this study were all asthma patients in the IGD room, the sample was 24 in the slow deep breathing exercise group with 5 times per minute for 3 minutes, 24 in the deep breathing exercise group with 6 minutes per minute for 3 minutes. The research instrument used pulse oximetry and observation sheet. Data were analyzed using paired sample t-test and mann whitney. From the research result, the median(minimum-maximum) value of oxygen saturation change in intervention group of slow deep breathing exercise was 1,00(1-3) while in the intervention group deep breathing exercise was 2,00 (1-4) (p = 0,027 <0,05) The change in oxygen saturation by using deep breathing exercise intervention is more effective than the intervention of slow deep breathing exercise ...